Morphological Analysis Of Coastal Settlements In Tanjung Piayu Tua Village, Batam City - Susanto Jefferson Teo; Lathifa Nursyamsu (International Journal of Architecture and Urbanism, 2026)
Tanjung Piayu Old Village in Batam City is an example of a coastal area that has experienced significant residential development. Piayu Old Village is one of the oldest areas in Batam City, which existed before the city developed as rapidly as it does now. Settlements in Tanjung Piayu not only function as places to live, but also as centre of economic activity that are vital for the lives of local people. However, with increasing population and space requirements, these settlements face serious challenges in terms of space management and infrastructure. This research aims to analyze the physical characteristics of settlements in Kampung Tua Tanjung Piayu. Through observation methods, this research will reveal growth patterns, changes in buildings, and their relationship with environmental conditions and socio-cultural activities of the community. The results of the research provide a comprehensive picture of the morphology of the Kampung Tua Tanjung Piayu settlement where the buildings in Kampung Tua Tanjung Piayu follow the coastline and the infrastructure is less than perfect because not all areas have asphalt roads, some still use red soil as roads.